SPORTCHILARNI MUSOBAQA SHAROITIDA PSIXOLOGIK TAYYORLASHNING METODIK AHAMIYATI (Conferencea, 2022)
Successful participation in competitions depends not only on the high level of physical, technical and tactical preparation of the athlete, but also on his psychological preparation. as a mandatory element, the athlete must prepare psychologically for certain conditions of sports activities in order to open reserve possibilities.